KONSTRUKSI MAKNA KETIDAKADILAN BERBASIS GENDER MENURUT SUDUT PANDANG AKTIVIS WOMEN’S MARCH BANDUNG - Duwy Sartika; Evi Novianti; Priyo Subekti (Fakultas Dakwah dan Komunikasi, 2019)
Gender inequality is a phenomenon that occurs in society without being denied. Women 's March activists who are also gender activists that oppose gender inequality with all their efforts have a lot of experience in fighting gender inequality and various motives in facing it all. The existence of individual experience in dealing with reality influences the individual's view of seeing the social world. Like their perspective in constructing the meaning of inequality. Therefore this research aims to find out how is the construction of the meaning of gender inequality base on the perspective of Women’s March Bandung activists. This research took five informants who became activists on gender issues such as activists from Women’s March Bandung. This research is qualitative research, a phenomenological approach and using the theory of phenomenology Alfred Schutz. With data collection techniques such as in-depth interviews, observation, literature study. And triangulators as validation and validity of data. The results of the research showed that the construction of the meaning of gender inequality gave results that showed an interactive based results between inequality and gender itself in this research with more than one factor. Namely, the concept of gender and patriarchy is the cause of the occurrence of gender injustice with all of its aspects. Then how is feminism as an ideology and movement against the cases of gender inequality? Motives and experiences become factors that influence informants in constructing the meaning of gender inequality. Motives here are divided into because of motive, and in order to motive, which influences them in taking action. Motives also influence their actions to produce various experiences, such as experience before declaring themselves as an activist of gender issues and their experience when they became activists of gender issues. The conclusion of this research showed that there is also an interactive relationship between each concept and model.